Financial matchmakers in credit markets with heterogeneous borrowers - Zsolt Becsi; Victor Li; Ping Wang (Federal Reserve Bank of Atlanta, 2000)
What happens when liquidity increases in credit markets and more funds are channeled from borrowers to lenders? We examine this question in a general equilibrium model where financial matchmakers help borrowers (firms) and lenders (households) search out and negotiate profitable matches and where the composition of heterogeneous borrowers adjusts to satisfy equilibrium entry conditions. We find that enhanced liquidity causes entry by all borrowers and tends to benefit low-quality borrowers disproportionately. However, liquid credit markets may or may not be associated with higher output and welfare. The result is determined by whether the effect of higher market participation outweighs that of lower average quality. The net effect depends crucially on the source of the liquidity shock (financial matching efficacy, productivity, or entry barriers).
Keywords: 330; Game theory; Financial markets; Liquidity (Economics)